PEMBUATAN APLIKASI KALKULATOR FINANSIAL PENDIDIKAN DAN PENSIUN PADA WEBSITE ALLIANZ.CO.ID DI PT GERBANG INDONESIA TEKNOLOGI: Creating of Education and Pension Financial Calculator Application on Allianz.co.id Website at PT Gerbang Indonesia Teknologi - Fatihatul Komariyah; Bayu Widodo; Handri Pangestiaji (IPB University, 2018)
ABSTRACT PT Gerbang Indonesia Teknologi is a technology and information service provider company. One of the services offered is web development. Allianz Indonesia is collaborating with PT Gerbang Indonesia Teknologi to develop its main website, Allianz.co.id. One of Allianz's services is an investment. The most important thing in achieving investment objectives is financial planning. Allianz created a calculation formula for compiling education and pension financial planning using the Microsoft Office Excel application. The problem is not everyone knows how to count using Microsoft Office Excel applications, and the calculation formula is quite complicated. Creating of education and pension financial calculator application is expected to help the community to analyze and prepare financial planning based on the needs of education costs and pension funds in the future, which can be accessed through the Allianz.co.id website.The Creating of education and pension financial calculator applications applying the Scrum method. Scrum is suitable for use in creating this application because of the short processing time and the small number of teams. Scrum's activities include determining the product backlog, sprint, and demos. The creating of this application uses the Pimcore CMS based on the Symfony Framework.Education and pension financial calculator application provides features for calculating the cost of education needed, calculating the investment in education costs needed, calculating the monthly living expenses in pension, calculating the pension funds needed, calculating the pension fund investment needed, and sending an email detailing the results of calculations. ABSTRAK PT Gerbang Indonesia Teknologi merupakan perusahaan penyedia jasa layanan teknologi dan informasi. Salah satu jasa layanan yang ditawarkan yaitu web development. Allianz Indonesia bekerja sama dengan PT Gerbang Indonesia Teknologi untuk mengembangkan website utamanya yaitu Allianz.co.id. Salah satu layanan Allianz yaitu investasi. Hal yang terpenting untuk mencapai tujuan investasi salah satunya melakukan perencanaan finansial. Allianz membuat formula perhitungan untuk menyusun perencanaan finansial pendidikan dan pensiun menggunakan aplikasi Microsoft Office Excel. Permasalahannya tidak semua orang mengetahui cara menghitung menggunakan aplikasi Microsoft Office Excel dan formula perhitungannya cukup rumit. Pembuatan aplikasi kalkulator finansial pendidikan dan pensiun diharapkan dapat membantu masyarakat untuk menganalisa dan menyusun perencanaan finansial berdasarkan kebutuhan biaya pendidikan dan dana pensiun di masa depan, yang dapat diakses melalui website Allianz.co.id.Pembuatan aplikasi kalkulator finansial pendidikan dan pensiun menerapkan metode scrum. Scrum cocok digunakan dalam pembuatan aplikasi ini karena waktu pengerjaan yang singkat dan jumlah tim yang sedikit. Kegiatan scrum meliputi penentuan product backlog, sprint, dan demo. Pembuatan aplikasi ini menggunakan CMS Pimcore dengan basis Symfony Framework.Aplikasi kalkulator finansial pendidikan dan pensiun menyediakan fitur untuk kalkulasi biaya pendidikan yang dibutuhkan, kalkulasi investasi biaya pendidikan yang dibutuhkan, kalkulasi biaya hidup bulanan pada masa pensiun, kalkulasi dana pensiun yang dibutuhkan, kalkulasi investasi dana pensiun yang dibutuhkan, dan kirim email rincian hasil kalkulasi.